Odpowiedź :
Chodzi o miejsca zerowe?
a) delta=b^2 - 4*a*c
delta= 4^2 - 4*1*1
delta= 16 - 4
delta= 12
x1= -b-pierwiastek z delty/2*a
x1=-4 - pierwiastek z 12/2
x2= -b+pierwiastek z delty/2*a
x2= -4+pierwiastek z 12/2
a) delta=b^2 - 4*a*c
delta= 4^2 - 4*1*1
delta= 16 - 4
delta= 12
x1= -b-pierwiastek z delty/2*a
x1=-4 - pierwiastek z 12/2
x2= -b+pierwiastek z delty/2*a
x2= -4+pierwiastek z 12/2
a) y=x²+4x+1
a=1
b=4
c=1
delta=b²-4ac
delta=16-4
delta=12
√delta=√12=2√3
x₁=(-b-√delta)/2a
x₁=(-4-2√3)/2
x₁=-2-√3
x₂=(-b+√delta)/2a
x₂=(-4+2√3)/2
x₂=-2+√3
b)y=-x²+3x+1
a=-1
b=3
c=1
delta=9+4
delta=13
√delta=√13
x₁=(-3-√13)/-2
x₁=3+√13/2
x₂=(-3+√13)/-2
x₂=3-√13/2
a=1
b=4
c=1
delta=b²-4ac
delta=16-4
delta=12
√delta=√12=2√3
x₁=(-b-√delta)/2a
x₁=(-4-2√3)/2
x₁=-2-√3
x₂=(-b+√delta)/2a
x₂=(-4+2√3)/2
x₂=-2+√3
b)y=-x²+3x+1
a=-1
b=3
c=1
delta=9+4
delta=13
√delta=√13
x₁=(-3-√13)/-2
x₁=3+√13/2
x₂=(-3+√13)/-2
x₂=3-√13/2